1991
DOI: 10.1182/blood.v77.5.1080.bloodjournal7751080
|View full text |Cite
|
Sign up to set email alerts
|

NB4, a maturation inducible cell line with t(15;17) marker isolated from a human acute promyelocytic leukemia (M3)

Abstract: Acute promyelocytic leukemia (APL) is a well-defined entity among acute leukemia, cytogenetically characterized by a t(15;17) (q22;q11–12) translocation. In vitro and in vivo studies suggest that all-trans retinoic acid (RA) treatment restores cell maturation. We have isolated the first permanent cell line with t(15;17), derived from the marrow of a patient with APL in relapse. The establishment of the cell line, its morphologic, karyotypic, and immunohistochemical features are reported. RA induced cell line m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
176
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(181 citation statements)
references
References 0 publications
5
176
0
Order By: Relevance
“…The human myeloid cell lines HL‐60 (Collins et al, 1977), NB4 (Lanotte et al, 1991), U‐937 (Sundstrom and Nilsson, 1976), and K562 (Lozzio and Lozzio, 1975), the human T cell leukemia cell line Molt‐4, and the human NK/T leukemia cell line YT‐indy were grown in RPMI 1640 culture medium supplemented with 10% heat‐inactivated FCS (FCS). The human embryonic kidney cell line 293T/17 and the epithelial cell line HeLa were grown in DMEM (DMEM) containing 10% FCS plus penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The human myeloid cell lines HL‐60 (Collins et al, 1977), NB4 (Lanotte et al, 1991), U‐937 (Sundstrom and Nilsson, 1976), and K562 (Lozzio and Lozzio, 1975), the human T cell leukemia cell line Molt‐4, and the human NK/T leukemia cell line YT‐indy were grown in RPMI 1640 culture medium supplemented with 10% heat‐inactivated FCS (FCS). The human embryonic kidney cell line 293T/17 and the epithelial cell line HeLa were grown in DMEM (DMEM) containing 10% FCS plus penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…NB4 is a relatively newly created promyelocytic leukaemia cell line established from a patient with acute promyelocytic leukaemia (APL; FAB classification, M3) 1 . Unlike HL‐60 cells, NB4 cells contain the clinically relevant t(15;17) translocation unique to APL patients 1 and present in 90% of these patients. This translocation creates a hybrid gene between the C‐terminus of the retinoic acid receptor‐α (RARα) and the N‐terminus of the promyelocytic leukaemia (PML) locus, resulting in a PML‐RARα fusion gene.…”
Section: Introductionmentioning
confidence: 99%
“…All‐ trans retinoic acid (ATRA) has been shown to play a role in granulocytic maturation, in particular in HL‐60 and NB4 cells 1 , 4 . In addition, the administration of ATRA has been used to treat patients with APL, 5 believed to be through ATRA‐induced differentiation of the leukaemic cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The NB4 cell line carried the t(15;17) translocation resulting in the joining of the promyelocytic leukemia‐associated protein (PML) oncogene to the gene encoding the retinoic acid receptor‐α (RARα). ( 13,14 ) It has been shown that the fusion gene plays a central role in leukemogenesis in APL and the presence of the PML/RARα fusion protein disrupts the normal location of the PML nuclear body and interferes with the function of PML for growth inhibition. ( 14 ) Previous studies have also demonstrated that NB4 cell line could be differentiated along granulocytic or monocyte/macrophage pathway by various differentiation inducers, providing an excellent model for studying cell differentiation.…”
mentioning
confidence: 99%